ANALISIS BIG DATA TERHADAP KELAYAKAN PENDIDIKAN JENJANG SEKOLAH DASAR DI INDONESIA TAHUN 2023-2024 - Irika Widiasanti; Nabila Annissa Permana; Nafisatul Barokah; Qonita Nailal Husna; Raihan Fajar Fauzi; Tirto Mareno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the feasibility of elementary education in Indonesiaduring 2023–2024 through the use of big data. The research employed a descriptivequantitative approach using secondary data from Kaggle sourced fromKemendikbudristek’s Data Portal. The analyzed variables included properclassrooms, classroom damage, teachers with bachelor’s degrees, dropout rates,and grade repetition rates. The results show that the quality of elementary educationin Indonesia remains unequal. Several provinces in eastern Indonesia haveinadequate educational facilities, high levels of classroom damage, and limitedqualified teachers. In addition, dropout and grade repetition rates in several regionsremain relatively high. These findings indicate the need for equal distribution ofeducational facilities and improvement of teacher quality to enhance elementaryeducation in Indonesia.